Pengaruh Kreativitas Produk Dan Keterampilan Berwirausaha Terhadap Keberhasilan Usaha UMKM Opak Ubi Di Desa Pegajahan - Dwi Tiara Sari; Muhammad Radiansyah (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2022)
The purpose of this study was to determine the effect of product creativity and entrepreneurship skills on the success of the Opak sweet potato business in Pegajahan village. The analysis used in this study is a quantitative and descriptive analysis by taking a sample of 32 small and medium-sized enterprises UMKM in Pegajahan village. The results of this study indicate the effect on the business success of cassava opaque UMKM as indicated by the multiple regression results, namely Y = 1.963 + 0.301X1 + 0.566X2 + e. From the results of the partial test of the product creativity variable on the success of the Opak yam UMKM, the value of tcount = 1.808 1.69 and the variable of entrepreneurial skills on business success obtained the value of tcount = 3.187 1.69, this shows that partially the variables of product creativity and entrepreneurship skills provide a positive and significant influence on the success of the sweet potato opaque business in Pegajahan village. The results of the F test obtained the value of FcountFtable (38.7233.327) with a probability level (0.010.05). The results of the coefficient of determination (R2) obtained a value of 0.728, this means that product creativity and entrepreneurial skills can increase business success by 72.8% and the remaining 27.2% is explained in other variables outside the study.